2014
DOI: 10.1002/ps.3759
|View full text |Cite
|
Sign up to set email alerts
|

Benchmark study on glyphosate‐resistant crop systems in the United States. Economics of herbicide resistance management practices in a 5 year field‐scale study

Abstract: Herbicide use strategies that include a diversity of herbicide mechanisms of action will increase the long-term sustainability of glyphosate-based weed management strategies. Growers can adopt herbicide resistance BMPs with confidence that net returns will not be negatively affected in the short term and contribute to resistance management in the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…It is possible to consider that the strategies for managing resistance and mitigation are well understood by producers, even if few strategies have been implemented, primarily considering the economic argument (Edwards et al, 2014). In most cases, producers have adopted the most convenient and economical management practices until a critical event promotes the paradigm shift (Burgos et al, 2013).…”
Section: Continued Use Of Rrmentioning
confidence: 99%
“…It is possible to consider that the strategies for managing resistance and mitigation are well understood by producers, even if few strategies have been implemented, primarily considering the economic argument (Edwards et al, 2014). In most cases, producers have adopted the most convenient and economical management practices until a critical event promotes the paradigm shift (Burgos et al, 2013).…”
Section: Continued Use Of Rrmentioning
confidence: 99%
“…[97] This means that growers can adopt BMP with confidence that they will not negatively affect their net returns in the short-term, and will help mitigate HR weed problem in the long-term. To provide similar practical examples in Europe, it is crucial that demonstration trials that include IWM practices integrated within crop rotation systems involving HT crops are supported.…”
Section: Demonstrate To Growers With Practical Examples That Bmp Leadmentioning
confidence: 99%
“…Indeed, numerous studies have highlighted that growers in the US are not fully committed to adopt mitigation strategies. [32,114] In the Benchmark Study in the Midwest and southern US, [97] the authors reported that the management of HR weeds based on integrated practices as recommended by academics was sustainable from economic and agronomic points of view, but the challenge was to convince growers to adopt such practices. They showed that alternative weed control strategies are not significantly accepted and adopted even by growers that were aware that these strategies would lead to better results.…”
Section: Foster Awareness-raising Programs and Coordinated Responsesmentioning
confidence: 99%
“…A 2011 survey in the Mid-South testified that some BMPs, particularly cultural practices, are implemented in a limited manner because of time constraints, weather, extra costs, and a certain difficulty for some farmers in adopting a proactive strategy when they have not experienced resistant weeds on their own farms (Riar et al 2013). Yet, a detailed benchmark study in more than a hundred farm fields, comparing costs, yields, and net returns between growers' standard weed management and BMPs, showed that, despite their higher costs, BMPs could lead to the same net returns (Edwards et al 2014). In a late 2012 survey of Certified Crop Advisors, 40 % said that farmers would only adopt BMPs if resistant weeds became a problem in their fields (Asmus et al 2013).…”
Section: Farmer Attitudesmentioning
confidence: 99%